Automatic Identification of Individual rpoB Gene Mutations Responsible for Rifampin Resistance in Mycobacterium tuberculosis by Use of Melting Temperature Signatures Generated by the Xpert MTB/RIF Ultra Assay - Cao, Yuan (J Clin Microbiol, 2019)
Molecular surveillance of rifampin-resistant Mycobacterium tuberculosis can help to monitor the transmission of the disease. The Xpert MTB/RIF Ultra assay detects mutations in the rifampin resistance-determining region (RRDR) of the rpoB gene by the use of melting temperature (T(m)) information from 4 rpoB probes which can fall in one of the 9 different assay-specified T(m) windows. The large amount of T(m) data generated by the assay offers the possibility of an RRDR genotyping approach more accessible than whole-genome sequencing. In this study, we developed an automated algorithm to specifically identify a wide range of mutations in the rpoB RRDR by utilizing the pattern of the T(m) of the 4 probes within the 9 windows generated by the Ultra assay. The algorithm builds a RRDR mutation-specific “T(m) signature” reference library from a set of known mutations and then identifies the RRDR genotype of an unknown sample by measuring the T(m) distances between the test sample and the reference T(m) values. Validated using a set of clinical isolates, the algorithm correctly identified RRDR genotypes of 93% samples with a wide range of rpoB single and double mutations. Our analytical approach showed a great potential for fast RRDR mutation identification and may also be used as a stand-alone method for ruling out relapse or transmission between patients. The algorithm can be further modified and optimized for higher accuracy as more Ultra data become available.